Mechanical characteristics of MHD of the non-Newtonian magnetohydrodynamic Maxwell fluid flow past a bi-directional convectively heated surface with mass flux conditions - Algehyne, Ebrahem A.; Lone, Showkat Ahmad; Raizah, Zehba; Eldin, Sayed M.; Saeed, Anwar; Galal, Ahmed M. (Frontiers in Materials, 2023)
In engineering and manufacturing industries, the stretching flow phenomena have numerous real-world implementations. The real-world applications related to the stretched flow models are metal-working, crystal growth processes, cooling of fibers, and plastics sheets, etc. Therefore, in this work, the mechanical characteristics of magnetohydrodynamic of the non-Newtonian Maxwell nanofluid flow through a bi-directional linearly stretching surface are explored. Brownian motion, thermophoresis and chemical reaction impacts are considered in this analysis. Additionally, the thermal convective and mass flux conditions are taken into consideration. The mathematical framework of the existing problem is constructed on the highly nonlinear PDEs. Suitable similarity transformations are used for the conversion of partial differential equations (PDEs) into ordinary differential equations (ODEs). The flow problem is tackled with homotopy analysis method which is capable to solve higher-order nonlinear differential equations. Different flow profiles against various flow parameters are discussed physically. Heat and mass transference mechanisms for distinct flow factors are analyzed in a tabular form. The outcomes showed that both the primary and secondary velocities are the declining functions of magnetic and Maxwell fluid parameters. The heat transfer rate rises with the cumulative values of Brownian motion and thermal Biot number. Also, the mass transfer rate decreases with the rising Schmidt number, Brownian motion parameter and chemical reaction parameter, while increases with the augmenting thermophoresis parameter. It has been highlighted that the streamlines in the current work for the Maxwell and Newtonian models are in fact different from one another.